2019
DOI: 10.1016/j.invent.2019.100277
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of internet-based cognitive-behavioural therapy for obsessive-compulsive disorder

Abstract: Economic analyses of treatments for OCD have been limited. This study analysed the comparative economic benefits and costs of an internet-based CBT (iCBT) relative to internet-based progressive relaxation therapy (iPRT) control. These were benchmarked against current estimates for face-to-face CBT (ffCBT) sourced from literature. The benefits to society of providing increased access to treatment was assessed using a cost-benefit analysis based upon productivity gains arising from treatment. Identification of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 29 publications
(51 reference statements)
0
25
0
Order By: Relevance
“…Therapist drift is a common pattern during face-to-face CBT sessions [ 73 ], hence, reduced therapist contact during interventions coulddecrease this phenomenon potentially. Moreover, technology-delivered interventions increase cost-effectiveness [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therapist drift is a common pattern during face-to-face CBT sessions [ 73 ], hence, reduced therapist contact during interventions coulddecrease this phenomenon potentially. Moreover, technology-delivered interventions increase cost-effectiveness [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the updated literature search, we identified 10 additional studies that met the inclusion criteria of our review and had been published over the preceding 2 years, [113][114][115][116][117][118][119][120][121][122] as shown in Figure 7. All 10 additional studies used DIs based on CBT delivered via the web/internet 113,114,[116][117][118][119]121,122 or via VR 120 or a mobile app. 115 One study used a non-CBT DI (progressive muscle relaxation).…”
Section: Updated Literature Searches and Additional Studies Retrievedmentioning
confidence: 99%
“…For instance, a cost‐utility analysis found that MindSpot was dominant relative to usual care when treating depression and anxiety — that is, it produced net cost savings and positive QALYs relative to the comparator (Lee et al 2017a). Only one cost‐effectiveness analysis has examined the impact of Mental Health Online when delivered to individuals with obsessive‐compulsive disorder (Osborne et al 2019). However, the interpretation of these study findings is hindered by the absence of an incremental analysis.…”
Section: What Is the ‘Output’ Of The Mental Health Sector And What Ismentioning
confidence: 99%